Islamic financial literacy program in Generation Z Islamic senior high school students - Zusryn, Alyta Shabrina; Rofi’i, Muhammad; Gani, Ariel Nian (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Indonesia's population has been dominated by young and Muslim people in recent years. However, these conditions are not comparable to the Islamic financial literacy level in Indonesia, which is still low. Therefore, there is a need for early education for young people who are in high school. This activity aims to provide an introduction and knowledge of Islamic finance to generation Z, namely, Islamic Senior High School (MAN) 3 Jakarta students. In its implementation, this workshop used video and game crossword puzzles to educate MAN 3 Jakarta students about Islamic finance. The results of the evaluation of this activity show that after the workshop, the number of students who answered correctly in the aspect of Islamic financial literacy drastically increased. After the workshop, the number of students who knew of Islamic financial institutions also increased. On the intention side, there is an increase in students' attractiveness to Islamic financial products and services. Therefore, educational workshops on Islamic finance need to be developed and carried out on a large scale not only for high school students but also for students and the public.